2020
DOI: 10.1016/j.msea.2020.139148
|View full text |Cite
|
Sign up to set email alerts
|

Ageing response of cold-rolled Al–Cu–Mg alloy

Abstract: This work presents a detailed investigation of the ageing behaviour of AA2519 alloy subjected to cold rolling with reduction of 10-80% (ε~0.11-1.61). The impact of pre-straining level and ageing duration on the mechanical performance was elucidated via hardness and tensile testing, DSC and analytical TEM. The increasing rolling reduction followed by ageing reduces the peak age hardening and pronounces softening under overageing. This effect of pre-strain on mechanical properties is related to the dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…Moreover, the selected-area diffraction (SAED) pattern taken from this area additionally exhibited the intensity maxima at 1/3 and 2/3 [220] α (red circles in the insert in Fig. 2a) attributable to the Ω-phase [16][17][18][19]. The TEM micrograph taken from the <011> α direction (Fig.…”
Section: Microstructure In the Base Materials Zonementioning
confidence: 92%
See 3 more Smart Citations
“…Moreover, the selected-area diffraction (SAED) pattern taken from this area additionally exhibited the intensity maxima at 1/3 and 2/3 [220] α (red circles in the insert in Fig. 2a) attributable to the Ω-phase [16][17][18][19]. The TEM micrograph taken from the <011> α direction (Fig.…”
Section: Microstructure In the Base Materials Zonementioning
confidence: 92%
“…pct.). This is a typical heat-treatable alloy whose precipitation path is studied relatively well [16][17][18][19]. The material was produced by ingot casting, homogenized at 510 � C for 24 h and then recrystallized by rolling at 425 � C to a true strain of 0.88.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cutting of θ phase was also observed in molecular dynamics (MD) studies using realistic models of interatomic interaction [33][34][35]. Depending on the aging conditions, the size of released θ precipitates can vary significantly, starting from a few nanometers in diameter and reaching hundreds of nanometers [23,32,36,37]. In the experimental work [32], it was shown that the cutting of θ phase has a threshold character: cutting of particles only with a size less than 60 nm was observed.…”
Section: Introductionmentioning
confidence: 90%